Determination of pore-lining residues in the hepatitis C virus p7 protein. - Chew, C; Vijayan, R; Chang, J; Zitzmann, N; Biggin, P (Cell Press, 2009)
The p7 protein from hepatitis C virus is critical for the assembly and secretion of infectious virus, making it an attractive drug target. It is thought to be a viroporin with a demonstrated ion channel activity when reconstituted into planar lipid bilayers. Electron microscopy experiments suggest that p7 oligomers coexist as hexamers and heptamers. Proposed models of p7 oligomers assume the N-terminal helix to be the pore lining helix. Here, we demonstrate, via electrophysiology, that Cu(2+) has an inhibitory effect on the p7 ion channel and that the amino acid responsible for this inhibition is one histidine in each monomer. This information coupled with the p7 sequence data suggests that the N-terminal helix of p7 does indeed form the transmembrane pore and that this histidine is pore-lining. The information will aid in the construction of oligomeric pore-models and the interpretation of electron microscopy data.